Blood pressure lowering and prevention of dementia: an individual patient data meta-analysis. (25th October 2022) - Peters, Ruth; Xu, Ying; Fitzgerald, Oisin; Aung, Htein Linn; Beckett, Nigel; Bulpitt, Christopher; Chalmers, John; Forette, Francoise; Gong, Jessica; Harris, Katie; Humburg, Peter; Matthews, Fiona E; et al.
Abstract: Aims: Observational studies indicate U-shaped associations of blood pressure (BP) and incident dementia in older age, but randomized controlled trials of BP-lowering treatment show mixed results on this outcome in hypertensive patients. A pooled individual participant data analysis of five seminal randomized double-blind placebo-controlled trials was undertaken to better define the effects of BP-lowering treatment for the prevention of dementia. Methods and results: Multilevel logistic regression was used to evaluate the treatment effect on incident dementia. Effect modification was assessed for key population characteristics including age, baseline systolic BP, sex, and presence of prior stroke. Mediation analysis was used to quantify the contribution of trial medication and changes in systolic and diastolic BP on risk of dementia. The total sample included 28 008 individuals recruited from 20 countries. After a median follow-up of 4.3 years, there were 861 cases of incident dementia. Multilevel logistic regression reported an adjusted odds ratio 0.87 (95% confidence interval: 0.75, 0.99) in favour of antihypertensive treatment reducing risk of incident dementia with a mean BP lowering of 10/4 mmHg. Further multinomial regression taking account of death as a competing risk found similar results. There was no effect modification by age or sex. Mediation analysis confirmed the greater fall in BP in the actively treated group was associated with a greater reduction in dementia risk. Conclusion: The first single-stage individual patient data meta-analysis from randomized double-blind placebo-controlled clinical trials provides evidence to support benefits of antihypertensive treatment in late-mid and later life to lower the risk of dementia. Questions remain as to the potential for additional BP lowering in those with already well-controlled hypertension and of antihypertensive treatment commenced earlier in the life-course to reduce the long-term risk of dementia. Classification of evidence: Class I evidence in favour of antihypertensive treatment reducing risk of incident dementia compared with placebo. Structured Graphical Abstract: Structured Graphical Abstract Action in Diabetes and Vascular disease: preterAx and diamicroN-MR Controlled Evaluation (ADVANCE). Hypertension in the Very Elderly Trial (HYVET). Perindopril Protection Against Recurrent Stroke Study (PROGRESS). Systolic Hypertension in the Elderly Program (SHEP). SYSTolic Hypertension in EURope Trial (SYST-EUR).